3-D digital outcrop model for analysis of brittle deformation and lithological mapping (Lorette cave, Belgium). (March 2019) - Triantafyllou, A.; Watlet, A.; Le Mouélic, S.; Camelbeeck, T.; Civet, F.; Kaufmann, O.; Quinif, Y.; Vandycke, S.
Abstract: Acquiring and building Digital Outcrop Models (DOM) becomes an essential approach in geosciences. This study highlights the strong potential of Structure-from-motion (SfM) photogrammetry for full-3D mapping of inaccessible outcrops, combining pictures captured from field and from unmanned aerial vehicle-embedded digital cameras. We present a workflow for (i) acquiring and reconstructing a DOM of a geometrically complex natural cave site using digital photogrammetry in a lowlight environment, (ii) georeferencing the 3D model in underground environments, (iii) identifying and characterizing the geometry of inaccessible geological structures and their tectonic kinematics (e.g., faults, joints, sedimentary bedding planes, slickenlines) for structural geology purposes. We illustrate our method by modelling a challenging case study: the main chamber of the Lorette cave (Rochefort Cave Laboratory, Belgium). First, we produced a high resolution, highly realistic model made of 395 million points cloud. This allowed to draw a detailed lithostratigraphic log of the exposed sedimentary pile, alternating decimetric carbonate mudstones with minor centimetric clay-rich layers. Secondly, we extract the orientation of brittle structures from the cave DOM which consist of joints, calcite-filled veins, fault planes with observable slickenlines and their kinematic indicators. Calcitic veins consist of tension gashes structures. Two subsets of tension gashes are distinguished based on their orientation (WNW-striking with low- vs subhorizontal dips) and morphology (planar vs en-echelon sigmoidal veins). Two faults subsets are identified: (i) a first one comprises south-dipping fault planes with mean strike-dip of N069-S42 and consist of bedding surface slip; (ii) a second one which corresponds to neoformed north-dipping faults (mean strike-dip: N279-N60). We recognize and characterize tectonic markers on fault planes directly from the high-resolution DOM (slickenlines and asymmetrical microscarps) pointing to a reverse shearing movement for all investigated faults. Based on their geometrical relations and fault-slip data, paleostress reconstruction points to a NW-SE to NNW-SSE subhorizontal compressive regime. This one is interpreted as the record of early phases of Variscan tectonics during the fold-to-fault progression. This research paper also highlights future possibilities for rapid semi-automatic interpretation of such 3D dataset for structural geology purposes as well as advances in technology and perspectives in terms of risk assessments and mitigation. Highlights: We applied the Sfm photogrammetry method to reconstruct a 395.4 million points cloud of the main chamber of Lorette cave (Belgium). This study provides an optimized workflow to acquire, reconstruct, georeference and extract structural and lithological data. This technique is a unique opportunity to acquire a high-resolution and photo-realistic 3D archive of inaccessible field outcrops.